ChemInform Abstract: One Pot InCl3‐Catalyzed Synthesis of 1‐Glycosylmethyl‐1H‐imidazoles. Issue 33 (27th July 2016) - Petrusova, Maria; Smrticova, Hana; Pribulova, Bozena; Vlckova, Silvia; Uhliarikova, Iveta; Docsa, Tibor; Somsak, Laszlo; Petrus, Ladislav
Abstract: A simple protocol allows the four component condensation of six different C‐glycosyl methylamines, 1, 2‐diketones, formaldehyde, and ammonium acetate to give imidazole substituted products such as (IV).